CONTINUOUS IMPROVEMENT OF DRILLING ULTRA-SHALLOW HORIZONTAL WELL THROUGH LEAN SIX SIGMA METHODOLOGY - Wahyudi, Petrus Tri; Yudoko, Gatot (JEMIS (Journal of Engineering & Management in Industrial System), 2019)
Low oil price environment impacted to business of Oil and Gas Company including PT. SDEC. However, PT. SDEC was able securing limited and fixed capital budget to drill well and had committed to drill certain well number to Government of Indonesia. When the initial 12 wells were completed with longer cycle time (average 9.9 days/well) than business plan (7.5 days/well) and also higher cost, the problem became more complex because company need to complete well as per commitment and in other hand no additional capital will be spent by parent company if actual expenditure exceeded the initial budget. Company assigned a team to solve the problem through Lean Six Sigma. Through strong collaboration among team, the project execution performance was improved (the Cp of drilling cycle time was improved from 0.06 to 1.08). As the result of this project save cost around $ 2.8 million.